2019
DOI: 10.1063/1.5124227
|View full text |Cite
|
Sign up to set email alerts
|

Cryogenic ion vibrational predissociation (CIVP) spectroscopy of a gas-phase molecular torsion balance to probe London dispersion forces in large molecules

Abstract: Cryogenic ion vibrational predissociation (CIVP) spectroscopy of a gas-phase molecular torsion balance to probe London dispersion forces in large molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 53 publications
(41 reference statements)
3
22
0
Order By: Relevance
“…Thermodynamic equilibrium means that both the monomers and dimers, in our case, must be volatile enough to establish a sufficient steady-state concentration, and thermally stable enough that they do not undergo a thermal reaction other than the reversible association. Consequently, high-temperature, high-pressure mass spectrometric determination of equilibria, as had been reported by Meot-Ner, can be used for a limited range of small molecules, or for unimolecular equilibria such as interconversion between conformers of a given ion . The temperature-dependent equilibria for pyridines/pyridinium ions versus their proton-bound dimers have provided bond dissociation energies for the parent pyridine and analogues with a limited range of small alkyl substituents .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Thermodynamic equilibrium means that both the monomers and dimers, in our case, must be volatile enough to establish a sufficient steady-state concentration, and thermally stable enough that they do not undergo a thermal reaction other than the reversible association. Consequently, high-temperature, high-pressure mass spectrometric determination of equilibria, as had been reported by Meot-Ner, can be used for a limited range of small molecules, or for unimolecular equilibria such as interconversion between conformers of a given ion . The temperature-dependent equilibria for pyridines/pyridinium ions versus their proton-bound dimers have provided bond dissociation energies for the parent pyridine and analogues with a limited range of small alkyl substituents .…”
Section: Discussionmentioning
confidence: 95%
“…A control experiment, based on an intramolecular competition, indicated that the high value, i.e., the 45 kcal/mol, is unlikely to be correct . We have reported a further independent experimental investigation of dispersion interactions based on gas-phase molecular torsion balances, and it also finds that the dispersion-corrected quantum chemical methods appear to overbind significantly . Given the magnitude of the discrepancy, the universality of London dispersion interactions, and the centrality of the determination to the confidence in experiment, theory, or both, we judged it imperative to validate the T-CID method itself with increasingly large molecules in the gas phase.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of 3,5-bis(3,5-di-tert-butylbenzyl)pyridine, used in the gas-phase studies here, was reported in our previous work. 10 The ions of interest were prepared upon electrospray ionization of a 10 -6 M methanol solution of the 3,5-bis(3,5-di-tert-butylbenzyl)pyridine. HPLC-grade methanol was purchased from Sigma-Aldrich and used without further purification.…”
Section: Methodsmentioning
confidence: 99%
“…Many characteristic chromophores, such as O-H or N-H stretching in complexes, can suffer from Fermi resonance with one or multiple otherwise dark overtones of low-lying modes in the investigated molecule. 37 Isotopic labeling is an effective technique to shift interacting vibration levels, and can easily be implemented via hydrogen-deuterium exchange by spraying from a deuterated, protic solvent. The isotopically substituted O-D and N-D modes move into the spectroscopically convenient, and otherwise nearly empty region between 2100 and 2700 cm −1 , making these chromophores easily distinguishable even from the otherwise nearby C-H stretching modes.…”
Section: Application For Labeled Organic Compoundsmentioning
confidence: 99%